Notary Responsibility For Forgetting Description in Assets or Letters According To Positive Laws in Indonesia - Reni Kurniawati; Budiyono Budiyono; Rahadi Wasi Bintoro; Hibnu Nugroho; Handri Wirastuti Sawitri (Authentica, 2021)
Notary profession is prone to legal entanglement. This is because notary internal factors such as carelessness, not complying with procedures, not carrying out professional ethics and external factors such as the behavior of the community. This research is intended to find out and analyze the limitations of the element of letter forgery by Notary Public and Notary Accountability for falsification of information in deed or letter according to positive law in Indonesia. Normative juridical research methods. The data source is secondary data. The results of the study in the form of narrative text. Analysis of legal materials used is qualitative normative. The results of the study showed the limitation of the element of forgery of letters by notary public, can be seen in terms of the actions of the perpetrators and the harmed parties. There is an element of wrongdoing made by the perpetrators and the injured parties are the parties in the deed made by notary public. Notary Accountability for falsification of information in deed or letter according to positive law in Indonesia there are three, namely criminal, civil, administrative / ethical accountability. Notary should be careful in carrying out its work so that there are no mistakes and harm to the parties so that it can cause sanctions in the form of accountability.Keywords: Notary, Letter Falsification, Accountability